Psychological Therapies for Thalassemia: Current Strategies - Alaa Fouad Almubarak et al. (International Journal of Scientific Research and Innovative Studies, 2024)
Thalassemia, a genetic blood disorder, presents significant physical and psychological challenges to patients due to its chronic nature and the demanding treatments required. Beyond medical management, the psychological burden associated with thalassemia, such as depression, anxiety, and reduced quality of life, necessitates tailored psychological interventions. This review explores current psychological therapy strategies employed to improve mental health outcomes for patients with thalassemia, including cognitive-behavioral therapy (CBT), family therapy, psychoeducation, and mindfulness-based approaches. The integration of these therapies alongside medical treatment is vital for holistic care and improved quality of life. Received Date: November 06, 2024 Accepted Date: November 27, 2024 Published Date: December 01, 2024 Available Online at https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/252 https://doi.org/10.5281/zenodo.14251274